Conductive paste for battery and preparation method thereof
By introducing modified epoxy resin, hyperbranched epoxy resin and multifunctional epoxy resin into the paste of HIT batteries, combining silver-nickel-copper powder and high-gloss silver powder, the high cost and compactness of HIT battery paste is solved. The poor performance has achieved low-cost and high-bonding conductive paste preparation, which has promoted the cost reduction and performance improvement of HIT batteries.
Patent Information
- Application Number
- CN202211615806.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-12-15
AI Technical Summary
The slurry required during the preparation of HIT batteries is high, and low-temperature cured silver paste is difficult to achieve high density and high adhesion, which limits the comprehensive promotion of HIT batteries.
Provide a low-temperature curable, low-cost, and high-bonding conductive paste, by introducing modified epoxy resin, hyperbranched epoxy resin and multifunctional epoxy resin, combined with silver-nickel-copper powder and high-gloss silver powder, A liquid curing agent and a surface additive were used to prepare a conductive paste with excellent adhesion and density.
It realizes low-cost and efficient preparation of HIT batteries, reduces silver content, improves the aging resistance and printing properties of the slurry, and meets the cost reduction requirements of HIT batteries.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0004000305190000021
Abstract
Description
Technical Field
[0001] The invention relates to a conductive paste for a battery and a preparation method thereof, belonging to the technical field of solar cell materials. Background Art
[0002] Heterojunction solar cells are also called intrinsic thin-film heterojunction cells. The English name is Heterojunction with Intrinsic Thin-layer, abbreviated as HIT. HIT cells are generally based on N-type silicon wafers. On the front side, there are transparent conductive oxide film (TCO for short), P-type amorphous silicon film and intrinsic hydrogen-rich amorphous silicon film; on the back side of the cell, there are TCO transparent conductive oxide film, N-type amorphous silicon film and intrinsic amorphous silicon film. Advantages of HIT cells: high conversion efficiency, low attenuation, low temperature coefficient, high bifaciality, etc. At present, more and more companies are deploying HIT, and industrialization is brewing. However, the slurry required in the preparation process of HIT cells is 1.5-2 times that of ordinary PERC solar cells, and its cost pressure limits its rapid promotion.
[0003] The transparent conductive oxide film used in HIT batteries limits the use of high-temperature sintering silver paste, and low-temperature curing paste must be used. Currently, the pastes on the market are basically pure silver, which are aging-resistant models, but the cost is high. HIT batteries have very high requirements for cost reduction, and pure silver is difficult to promote on a large scale. Other low-cost powders such as silver-copper have poor aging resistance (caused by incomplete coating and high oxygen content), silver-nickel has poor conductivity, nickel-copper has poor aging resistance, graphite is conductive and it is difficult to add large quantities, etc., which limit the comprehensive promotion of HIT batteries.
[0004] In order to ensure high conductivity and high density of the silver grid line, high-temperature silver paste is sintered at about 800℃, while low-temperature silver paste is difficult to sinter at 150-200℃ (resin volatilization). Generally, high density is achieved by compounding the size and shape of silver powder particles and adjusting the amount of addition. Generally speaking, the higher the powder content, the higher the density, but the higher the powder content, the correspondingly, the lower the resin content, which leads to worse adhesion to the substrate.
[0005] Therefore, there is a need for a conductive paste that can be cured at low temperature, has low cost and high adhesion for the preparation of HIT batteries. Summary of the invention
[0006] In view of the above problems in the prior art, the present invention provides a low-temperature curing, low-cost, high-adhesion conductive paste for HIT solar cells and a preparation method thereof, which can effectively reduce the silver content and reduce the cost, and can effectively promote the cost reduction requirements of HIT batteries.
[0007] The technical solution of the present invention to solve the above technical problems is as follows: a conductive paste for a battery, comprising the following raw materials in parts by weight: 0.5-3 parts of a modified epoxy resin, 0.5-3 parts of a hyperbranched epoxy resin, 0.5-2 parts of a multifunctional epoxy resin, 0.5-1.2 parts of a curing agent, 0.5-4 parts of an organic solvent, 0.1-0.5 parts of a surface additive, 0.1-1 parts of a thixotropic agent, 50-70 parts of silver-nickel-copper powder, and 10-30 parts of high-brightness silver powder.
[0008] On the basis of the above technical solution, the present invention can also make the following improvements:
[0009] Further, the modified epoxy resin has the following structure:
[0010]
[0011] The modified epoxy resin can effectively improve the adhesion to the substrate. The synthesis route of the modified epoxy resin is as follows:
[0012]
[0013] Furthermore, the multifunctional epoxy resin is one of a trifunctional epoxy resin and a tetrafunctional epoxy resin, or a mixture of the two.
[0014] Furthermore, the silver-nickel-copper powder contains 15%-25% silver, 5%-20% nickel and 60%-80% copper, has a particle size of no more than 15 μm and is spherical in shape.
[0015] Furthermore, the silver powder is bright silver powder, and the particle size does not exceed 10 μm.
[0016] Furthermore, the surface additive is one or more of phosphoric acid type monoalkoxy titanate, composite phosphoric acid type monoalkoxy titanate, epoxy silane and the like.
[0017] Furthermore, the thixotropic agent is hydrophobic silica or paraffin.
[0018] Furthermore, the curing agent is high temperature resistant dicyandiamide.
[0019] Furthermore, the organic solvent is one or more of diethylene glycol monobutyl ether, terpineol, diethylene glycol butyl ether acetate, diethylene glycol butyl ether and dimethyl adipate.
[0020] The present invention also discloses a method for preparing the conductive paste for a battery as described above, comprising the following steps:
[0021] Add modified epoxy resin, hyperbranched epoxy resin, multifunctional epoxy resin, curing agent, organic solvent, surface additive, thixotropic agent, silver-nickel-copper powder and silver powder into a mixing kettle in order according to weight portions, control the temperature at 15-45°C, stir at 200-500r / min, stir for 1-3h, and finally evacuate for 0.2-1h to obtain.
[0022] Further, the preparation of the silver-nickel-copper powder comprises the following steps:
[0023] (1) Surface treatment of copper powder:
[0024] The spherical copper powder is placed in a solution containing sodium hydroxide and fatty alcohol polyoxyethylene ether, fully stirred, and then the copper powder is filtered out, added to a dilute hydrochloric acid solution, ultrasonically treated, repeatedly washed, and filtered to obtain wet copper powder;
[0025] (2) Nickel copper plating process:
[0026] In a container, add a mixture of ethylene glycol, propylene glycol and ultrapure water, then add the copper powder obtained in step (1), then add polyvinyl pyrrolidone and nickel acetate tetrahydrate, stir well to form a suspension; then add hydrazine hydrate and sodium hydroxide solution, stir, adjust the pH value to 11, continue the reaction, precipitate to obtain a coarse powder, and wash to obtain a wet nickel-coated copper powder;
[0027] (3) Nickel silver plating process:
[0028] Dissolve silver nitrate in deionized water, add ammonia water to make the silver ammonia solution clear, add ethylenediaminetetraacetic acid and polyvinyl pyrrolidone to the silver ammonia solution and stir evenly;
[0029] Add hydrazine hydrate to deionized water to prepare a reducing solution;
[0030] The nickel-coated copper powder obtained by the treatment in the above step (2) is poured into a silver-ammonia mixed solution, stirred and dispersed, the pH value is adjusted to 10, the temperature is controlled at 30-70° C., and the reducing solution is slowly added dropwise, and the dripping is completed within 0.5 hours. The reaction is continued for 1-3 hours. After the reaction, silver-nickel-copper powder is generated, which is washed, filtered and dried to obtain silver-nickel-copper powder.
[0031] The present invention reduces the brittleness of the cured product by introducing a hyperbranched epoxy resin. The epoxy resin itself is relatively brittle; the silver paste with high powder and low resin content is more brittle after curing, and is very prone to cracking under the impact of cold and heat at -40°C to 85°C. The addition of the hyperbranched epoxy resin can significantly improve this shortcoming.
[0032] The present invention improves the strength of the resin itself by introducing a multifunctional epoxy resin, thereby ensuring that the strength of the resin itself can support the damage caused by the later welding tension.
[0033] The present invention adopts the liquid curing agent dicyandiamide mainly because bubbles are easily generated in the solid or powder curing agent during the curing process, which affects the compactness after curing. The liquid curing agent can well avoid this phenomenon.
[0034] The invention adopts silver-nickel-copper two-layer coating, which not only reduces the cost but also overcomes the disadvantage that silver and copper have poor aging resistance.
[0035] The non-sintered paste prepared by the present invention will cause resin aging and yellowing of the powder surface during long-term use. The yellowing of the grid line will affect the appearance and secondly the photoelectric conversion efficiency. The present invention can increase the aging resistance and reduce the yellowing problem of the silver paste during long-term use by adding a certain proportion of high-brightness silver powder.
[0036] In addition, the powder is made of spherical powder material. By controlling the particle size of the powder, the density of the HIT low-temperature silver paste after solidification and sintering can be effectively improved, thereby reducing the volume resistivity of the formed silver layer. The silver layer has high density and good adhesion, which is beneficial to improving the power of the component; and the use of spherical powder is conducive to the rapid printing of the paste (>300mm / s).
[0037] The present invention reduces the viscosity of the system by adding a surface treatment agent, increases the addition amount, and is also beneficial to improving the solidification density.
[0038] The present invention improves printing processability and storage stability by adding a thixotropic agent. The prepared silver paste needs a certain viscosity and thixotropy to ensure good printability of the silver paste. Low viscosity and low thixotropy will result in wide printed grid lines. High viscosity and high thixotropy will result in uneven printed grid lines, making it difficult to meet the aspect ratio of the rubber strip. Secondly, low viscosity and low thixotropy will cause the powder to easily settle, which is not conducive to storage, and the powder will settle after curing.
[0039] The advantages of the present invention are: the conductive paste of the present invention has the characteristics of low-temperature curing, low cost and high adhesion. The present invention can effectively improve the adhesion to the substrate by introducing modified epoxy resin, and the hyperbranched epoxy resin can improve its toughness. The low-cost silver-nickel-copper powder can not only ensure the aging resistance of its powder, but also effectively reduce the cost of pure silver powder. The addition of high-brightness silver powder ensures that its color does not turn yellow after aging. The conductive paste prepared by the present invention can effectively reduce the silver content and reduce the cost, and can effectively promote the cost reduction requirements of HIT batteries. DETAILED DESCRIPTION
[0040] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0041] In the examples of the present invention, unless otherwise specified, all raw materials used are commercially available chemicals.
[0042] 1. Preparation of modified epoxy resin:
[0043] Take 2 mol of PM-2 (2-hydroxyethyl methacrylate phosphate) and 2 mol of GMC (glycidyl methacrylate) and add them to a three-necked flask. After fully mixing, add 0.01 mol of bis(3-methoxybutyl)peroxydicarbonate, control the temperature at 20-30°C and stir for 12 hours to allow the reaction to be complete, and obtain the modified epoxy resin.
[0044] 2. Preparation of Silver-Nickel-Copper Powder
[0045] (1) Surface treatment of copper powder:
[0046] 300 g of spherical copper powder with a particle size of 3.5 μm was placed in 200 g of a solution containing 5% sodium hydroxide and 2% fatty alcohol polyoxyethylene ether (deoxygenated), and then ultrasonically stirred for 1 hour, the ultrasonic wave was turned off and continued to stir for 10 minutes, and then the copper powder was filtered out, added to a dilute hydrochloric acid solution (deoxygenated) with a pH value of 3, and ultrasonically treated for 0.5 hours, and then repeatedly washed with ultrapure water (deoxygenated), and the wet copper powder was obtained after filtration, and vacuum-sealed and stored for later use.
[0047] (2) Nickel copper plating process:
[0048] In a three-necked flask, add 400g of a mixture (deoxygenated) of ethylene glycol: glycerol: ultrapure water in a ratio of 30:10:400, then add 200g of the above-treated copper powder, then add 20g of PVP30 (polyvinyl pyrrolidone), 68g of nickel acetate tetrahydrate, fully stir under vacuum -0.1MPa to form a suspension, then nitrogen protection pressure relief and seal. Then add 140mL of 85wt% hydrazine hydrate and 200ml of 15mol / L sodium hydroxide solution after deoxygenation, under -0.1MPa, stir at 60°C and 500r / min for 0.5h, then nitrogen pressure relief, continuously add 15mol / L sodium hydroxide solution until the pH value is stable at 11, continue to react for 1h, precipitate to obtain coarse powder, then wash twice with water and ethanol to obtain wet nickel-coated copper powder.
[0049] (3) Nickel silver plating process:
[0050] Dissolve 23.6g of silver nitrate in 236g of deionized water, add ammonia water until the silver ammonia solution is just clear, add 3.5g of EDTA (ethylenediaminetetraacetic acid) and 11.8g of PVP30 to the silver ammonia solution, stir evenly, evacuate under vacuum, and seal with nitrogen pressure relief protection;
[0051] 200 mL of 85 wt% hydrazine hydrate was added to deionized water to prepare a reducing solution, and the solution was evacuated by vacuum and sealed with nitrogen pressure relief.
[0052] Pour 100g of nickel-coated copper powder obtained by the above step (2) into the silver-ammonia mixed solution, stir and disperse evenly, add sodium hydroxide solution to adjust the pH value to 10, control the heating temperature to 30-70°C, slowly drip the reducing solution, drip it within 0.5 hours, vacuum degree -0.1Mpa, control the stirring speed to 300r / min, and then continue to react for 2h, generate silver-nickel-copper powder after the reaction, then wash with deionized water and ethanol solution for 3 times, filter, dry at 80°C for 2h, and obtain silver-nickel-copper powder with a content of silver (15%-25%), nickel (5%-20%), and copper (60%-80%), with a particle size not exceeding 15μm and an average particle size of 2-6μm. Store in sealed containers.
[0053] Example 1
[0054] 2.5 parts of the above-mentioned homemade modified epoxy resin, 2 parts of hyperbranched epoxy resin (Hyper102), 0.5 parts of epoxy resin (AFG-90), 0.5 parts of liquid dicyandiamide, 4 parts of diethylene glycol butyl ether acetate, 0.2 parts of composite phosphoric acid type monoalkoxy titanate, 0.5 parts of gas silicon (R202), 65 parts of the above-mentioned homemade silver-nickel-copper powder, and 30 parts of bright silver powder (PSP-640) were added to a mixing kettle in sequence, the temperature was controlled at 20-40°C, the stirring speed was 300r / min, the mixture was stirred for 2h, and finally vacuumed for 0.5h and the discharge was tested.
[0055] Example 2
[0056] 2.5 parts of the above-mentioned homemade modified epoxy resin, 1 part of hyperbranched epoxy resin (Hyper102), 2.5 parts of epoxy resin (AFG-90), 0.5 parts of liquid dicyandiamide, 4 parts of diethylene glycol butyl ether acetate, 0.2 parts of composite phosphoric acid type monoalkoxy titanate, 0.5 parts of gas silicon (R202), 70 parts of the above-mentioned homemade silver-nickel-copper powder, and 30 parts of bright silver powder (PSP-640) were added to a mixing kettle in sequence, the temperature was controlled at 20-40°C, the stirring speed was 300r / min, the mixture was stirred for 2h, and finally vacuumed for 0.5h and the discharge was tested.
[0057] Example 3
[0058] 1.5 parts of the above-mentioned homemade modified epoxy resin, 2 parts of hyperbranched epoxy resin (Hyper102), 1.5 parts of epoxy resin (AFG-90), 0.5 parts of liquid dicyandiamide, 4 parts of diethylene glycol butyl ether acetate, 0.2 parts of composite phosphoric acid type monoalkoxy titanate, 0.5 parts of gas silicon (R202), 70 parts of the above-mentioned homemade silver-nickel-copper powder, and 30 parts of bright silver powder (PSP-640) were added to a mixing kettle in sequence, the temperature was controlled at 20-40°C, the stirring speed was 300r / min, the stirring was carried out for 2h, and finally vacuumed for 0.5h and the discharge was tested.
[0059] Example 4
[0060] 2.5 parts of the above-mentioned homemade modified epoxy resin, 2 parts of hyperbranched epoxy resin (Hyper102), 0.5 parts of epoxy resin (AFG-90), 0.5 parts of granular dicyandiamide, 4 parts of diethylene glycol butyl ether acetate, 0.2 parts of coupling agent γ-(2,3-epoxypropoxy)propyltrimethoxysilane (Kh-560), 0.5 parts of gas silicon (R202), 70 parts of the above-mentioned homemade silver-nickel-copper powder, and 30 parts of bright silver powder (PSP-640) were added to a mixing kettle in sequence, the temperature was controlled at 20-40°C, the stirring speed was 300r / min, the stirring was carried out for 2h, and finally vacuumed for 0.5h and the discharge was tested.
[0061] Comparative Example 1
[0062] 2.5 parts of epoxy resin (E51), 2 parts of hyperbranched epoxy resin (Hyper102), 0.5 parts of epoxy resin (AFG-90), 0.5 parts of liquid dicyandiamide, 4 parts of diethylene glycol butyl ether acetate, 0.2 parts of Kh-5600, 65 parts of the above-mentioned homemade silver-nickel-copper powder, and 30 parts of 2-3 μm ordinary silver powder were added to a mixing kettle in sequence, the temperature was controlled at 20-40°C, the stirring speed was 300 r / min, the mixture was stirred for 2 h, and finally vacuumed for 0.5 h and the discharge was tested.
[0063] Comparative Example 2
[0064] 2.5 parts of the above-mentioned homemade modified epoxy resin, 2 parts of hyperbranched epoxy resin (Hyper102), 0.5 parts of epoxy resin (AFG-90), 0.5 parts of liquid dicyandiamide, 4 parts of diethylene glycol butyl ether acetate, 0.2 parts of composite phosphoric acid type monoalkoxy titanate, 65 parts of commercially available silver-copper powder, and 30 parts of bright silver powder (PSP-640) were added to a mixing kettle in sequence, the temperature was controlled at 20-40°C, the stirring speed was 300r / min, the mixture was stirred for 2h, and finally vacuumed for 0.5h and the discharge was tested.
[0065] The products prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to performance tests, and the test items were as follows:
[0066] (1) Conductivity test:
[0067] The prepared slurry was coated on a glass slide with the length, width and thickness being 70 mm, 2 mm and 0.04 mm respectively. It was placed in an oven and cured at 175°C for 30 min. Then it was naturally cooled to room temperature and the volume resistivity was tested.
[0068] (2) Aging resistance test:
[0069] The cured adhesive strip was placed in an oven at 150°C and aged for 1000 h, then taken out to test the volume resistivity and color change of the adhesive strip.
[0070] (3) Bond strength test
[0071] Sample preparation: Fix the bare chip with TCO cells on it on a glass slide (to prevent debris), then apply glue on one of the slides, and stick the other one on top, with an overlapping area of 20mm*20mm, fix it, put it in an oven and heat it up to 175℃ at 10℃ / min, keep the temperature and cure for 30 minutes. Cool it down naturally to room temperature to test the shear strength, the unit of bonding strength is Mpa.
[0072] (4) Printability test
[0073] Use 40μm aperture screen printing at a speed of 300mm / s to observe whether the line is broken and whether the surface is smooth and concave after curing.
[0074] The test results are shown in Table 1:
[0075] Table 1 Product performance index table of embodiments and comparative examples
[0076]
[0077] It can be seen from the performance data in Table 1 that the low-temperature slurry prepared by the present invention has the advantages of low-temperature curing, low cost, high adhesion, and aging resistance. It improves the performance of the HIT battery while reducing the production cost of the HIT battery, and can effectively promote the cost reduction requirements of the HIT battery.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A conductive paste for a battery, characterized in that: The invention comprises the following raw materials in parts by weight: 0.5-3 parts of modified epoxy resin, 0.5-3 parts of hyperbranched epoxy resin, 0.5-2 parts of multifunctional epoxy resin, 0.5-1.2 parts of curing agent, 0.5-4 parts of organic solvent, 0.1-0.5 parts of surface additive, 0.1-1 parts of thixotropic agent, 50-70 parts of silver-nickel-copper powder, and 10-30 parts of high-brightness silver powder; The modified epoxy resin has the following structure: ; The synthetic route of the modified epoxy resin is as follows: ; The multifunctional epoxy resin is one of a trifunctional epoxy resin and a tetrafunctional epoxy resin, or a mixture of the two; The silver-nickel-copper powder contains 15%-25% silver, 5%-20% nickel and 60%-80% copper, and its particle size does not exceed 15 μm, and its shape is spherical powder; The silver powder is bright silver powder, and the particle size does not exceed 10 μm.
2. The conductive paste for battery according to claim 1, characterized in that: The surface additive is one or both of phosphoric acid type monoalkoxy titanate and composite phosphoric acid type monoalkoxy titanate.
3. The conductive paste for battery according to claim 1, characterized in that: The thixotropic agent is hydrophobic silica or paraffin.
4. The conductive paste for battery according to claim 1, characterized in that: The curing agent is high temperature resistant dicyandiamide.
5. A method for preparing a conductive paste for a battery according to any one of claims 1 to 4, characterized in that: The following steps are involved: Add modified epoxy resin, hyperbranched epoxy resin, multifunctional epoxy resin, curing agent, organic solvent, surface additive, thixotropic agent, silver-nickel-copper powder and silver powder into a mixing kettle in order according to weight portions, control the temperature at 15-45°C, stir at 200-500r / min, stir for 1-3h, and finally evacuate for 0.2-1h to obtain.
6. The method for preparing a conductive paste for a battery according to claim 5, characterized in that: The preparation of the silver-nickel-copper powder comprises the following steps: (1) Surface treatment of copper powder: The copper powder is placed in a solution containing sodium hydroxide and fatty alcohol polyoxyethylene ether, fully stirred, and then the copper powder is filtered out, added to a dilute hydrochloric acid solution, ultrasonically treated, repeatedly washed, and filtered to obtain wet copper powder; (2) Nickel copper plating process: In a container, add a mixture of ethylene glycol, propylene glycol and ultrapure water, then add the copper powder obtained in step (1), then add polyvinyl pyrrolidone and nickel acetate tetrahydrate, stir thoroughly to form a suspension; then add hydrazine hydrate and sodium hydroxide solution, stir, adjust the pH value to 11, continue the reaction, precipitate to obtain a coarse powder, and wash to obtain a wet nickel-coated copper powder; (3) Nickel silver plating process: Dissolve silver nitrate in deionized water, add ammonia water to make the silver ammonia solution clear, add ethylenediaminetetraacetic acid and polyvinyl pyrrolidone to the silver ammonia solution and stir evenly; Add hydrazine hydrate to deionized water to prepare a reducing solution; The nickel-coated copper powder obtained by the treatment in the above step (2) is poured into the silver-ammonia mixed solution, stirred and dispersed, the pH value is adjusted to 10, the temperature is controlled at 30-70°C, and the reducing solution is slowly added dropwise, and the dripping is completed within 0.5 hours. The reaction is continued for 1-3 hours. After the reaction, silver-nickel-copper powder is generated, which is washed, filtered and dried to obtain silver-nickel-copper powder.
Citation Information
Patent Citations
High-temperature-resistant silver-coated and nickel-coated copper conductive powder of core-shell structure and preparation method thereof
CN105598467A
Epoxy acrylic resin, and preparation method and applications thereof
CN109988283A
A low-temperature curing conductive silver paste for high-efficiency HJT batteries and its preparation method
CN114937518A